The effect of holiday haemodialysis treatments on patient mood, adverse symptoms and subjective wellbeing using the Big Red Kidney Bus. Issue 2 (February 2017) - Sims, Jane; Bennett, Paul N; Ockerby, Cherene; Ludlow, Marie; Fairbairn, Jo; Wilson, Anne; Kerr, Peter G
Abstract: Background and Aims: People with end‐stage kidney disease receiving haemodialysis are restricted to holidays where dialysis services are readily available. Holiday dialysis in regional, rural and remote areas is particularly challenging. The aims of this study were to evaluate the wellbeing of those who received dialysis in a holiday haemodialysis bus and to measure patient well‐being with that of a comparable cohort of haemodialysis patients. Methods: A three machine haemodialysis bus, the Big Red Kidney Bus, was built to enable people, their families and carers to take holidays across a range of tourist destinations in Victoria, Australia. Measures included pre‐post subjective well‐being, dialysis symptoms and mood questionnaires complemented by post semi‐structured telephone interviews. Results: Participating holidaymakers were positive about the haemodialysis bus service and the standard of care experienced. They reported decreased dialysis side effects of fatigue, muscle cramp and dry skin. The overall number of reported symptoms decreased, and the perceived level of bother associated with symptoms also decreased. No changes in subjective well‐being and mood were detected. Mean Personal Wellbeing Index scores were significantly higher than in a comparative haemodialysis sample. Conclusion: The Big Red Kidney Bus provided a safe and feasible holiday dialysis service. Holidaymakers' well‐being was reflected by the decreased dialysis patient side effects. Summary at a Glance: The authors explore the impact of holiday hemodialysis on patients' wellbeing, dialysis symptoms and mood status and demonstrated a successful model of holiday dialysis that can be facilitated in other parts of the world.